2009
DOI: 10.1371/journal.pone.0005049
|View full text |Cite
|
Sign up to set email alerts
|

Ste20-Related Proline/Alanine-Rich Kinase (SPAK) Regulated Transcriptionally by Hyperosmolarity Is Involved in Intestinal Barrier Function

Abstract: The Ste20-related protein proline/alanine-rich kinase (SPAK) plays important roles in cellular functions such as cell differentiation and regulation of chloride transport, but its roles in pathogenesis of intestinal inflammation remain largely unknown. Here we report significantly increased SPAK expression levels in hyperosmotic environments, such as mucosal biopsy samples from patients with Crohn's disease, as well as colon tissues of C57BL/6 mice and Caco2-BBE cells treated with hyperosmotic medium. NF-κB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 96 publications
(144 reference statements)
3
20
0
Order By: Relevance
“…The mice showed a decreased intestinal barrier function. 46 We have previously demonstrated that SLK expression and activity increase in the developing kidney and in kidneys subjected to ischemia-reperfusion injury. 7 The upregulation of expression may then favor homodimerization and phosphorylation, and possibly reversal of auto-inhibition, together leading to an increase in kinase activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mice showed a decreased intestinal barrier function. 46 We have previously demonstrated that SLK expression and activity increase in the developing kidney and in kidneys subjected to ischemia-reperfusion injury. 7 The upregulation of expression may then favor homodimerization and phosphorylation, and possibly reversal of auto-inhibition, together leading to an increase in kinase activity.…”
Section: Discussionmentioning
confidence: 97%
“…46 Cultured intestinal epithelial cells stably transfected with SPAK showed increased permeability. Transgenic mice that expressed a constitutively active form of SPAK under the control of the villin gene locus control region, which can target SPAK expression only in intestinal epithelial cells were generated to study intestinal barrier function in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal permeability was assessed in vivo (51). In brief, Pggt-Iβ TiΔIEC and control mice were deprived of food and water for 4 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear Run-on Assay-Nuclear run-on assay was performed according to the protocol of Dr. Yan (14). Briefly, nuclei were isolated from T84 cells that were untreated or treated with 10 ng/ml TNF-␣ for 2-4 h. Cells (5 ϫ 10 7 ) were pelleted in a test tube and washed twice with ice-cold phosphate-buffered saline.…”
Section: Methodsmentioning
confidence: 99%